THE EFFECT OF A TRIPOD CANE ON THE FUNCTIONAL MOBILITY OF PATIENTS WITH KNEE OSTEOARTHRITIS - Nelson Sudiyono (Faculty of Medicine Universitas Kristen Duta Wacana, 2020)
Background: Canes have been recommended as walking aids for knee osteoarthritis to reduce the loading on the affected knee. Patients are usually recommended to hold the cane in the contralateral hand to the affected knee. Nevertheless, some patients prefer to hold the cane ipsilateral to the affected knee. However, the effect of using ipsilateral or contralateral tripod cane on functional mobility in patients with knee osteoarthritis is still unknown Objective: To compare the immediate effect of ipsilateral and contralateral tripod cane usage on functional mobility in patients with symptomatic knee osteoarthritis Method: This cross-sectional study involved 30 overweight or obese patients with symptomatic unilateral or bilateral knee osteoarthritis (Kellgren Lawrence grade 2 and 3) who never use a cane. Functional mobility was evaluated with Time Up and Go test in three conditions; without walking aid, with tripod cane contralateral and ipsilateral to the more painful knee. Results: The TUG time of aid-free walking is 4.75 (p < 0.001, 95% CI 3.79 - 5.71) seconds faster than ipsilateral cane use and 6.69 (p < 0.001, 95%CI 5.35 - 8.03) seconds faster than contralateral cane use. The TUG time of ipsilateral cane use is 1,94 (95% CI, 1.13 - 2.79) seconds faster than contralateral. Conclusion: Patients with symptomatic knee OA who use tripod cane ipsilateral to the more painful knee have higher functional mobility than the contralateral.